2017
DOI: 10.18388/abp.2016_1343
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq-based analysis of differential gene expression associated with hepatitis C virus infection in cell culture

Abstract: Hepatitis C virus (HCV) infection is one of the major causes of chronic liver diseases. Unfortunately, the mechanisms of HCV infection-induced liver injury and host-virus interactions are still not well recognized. To better understand these processes we determined the changes in the host gene expression that occur during HCV infection of Huh-7.5 cells. As a result, we identified genes that may contribute to the immune and metabolic cellular responses to infection. Pathway enrichment analysis indicated that HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Herpes simplex virus also produces the ICP27 protein which mediates the stabilization of AU-rich element-containing host transcript ( 3 ) and Epstein-Barr virus infection leads to the stabilization of mRNAs through the activation of the stress activated protein kinase p38 ( 41 ). Several studies found differential host gene expression in cell cultures infected with HCV using high-throughput approaches and screens ( 42–46 ), but the mechanism of how the host gene expression is regulated by the virus is not well understood. Luna et al proposed that microRNA-122 sequestration by HCV RNA may lead to stabilization of miR-122 targets, facilitating the oncogenesis of HCV ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Herpes simplex virus also produces the ICP27 protein which mediates the stabilization of AU-rich element-containing host transcript ( 3 ) and Epstein-Barr virus infection leads to the stabilization of mRNAs through the activation of the stress activated protein kinase p38 ( 41 ). Several studies found differential host gene expression in cell cultures infected with HCV using high-throughput approaches and screens ( 42–46 ), but the mechanism of how the host gene expression is regulated by the virus is not well understood. Luna et al proposed that microRNA-122 sequestration by HCV RNA may lead to stabilization of miR-122 targets, facilitating the oncogenesis of HCV ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes contain both PrP protein and TSE infectivity [217,220], but deep sequencing indicates that they contain a select group of cellular nucleic acids, of which ~ 50% are retroelement RNAs [221]. Figure adapted, with permission, from reference [221] Second, PrP expression is upregulated in vitro by infection with adenovirus 5 [156,157], Epstein-Barr virus (EBV) [158], hepatitis C virus [159,160], HIV-1 [161], Helicobacter pylori [162], and Mycobacterium bovis [163], as well as by murine leukemia virus (MuLV) and vesicular stomatitis virus [164]. In vivo, brain PrP is upregulated in HIV-1 infection as well as in simian immunodeficiency virus (SIV) encephalitis in macaques [165].…”
Section: Prp Displays Antimicrobial Activitymentioning
confidence: 99%
“…Moreover, we used published transcriptomic data to further investigate the potential of several top age-distorter candidates to interfere with cellular senescence. We took advantage of the recent demonstration that human cellular senescence can be empirically deduced from transcriptomes through differential expression of a set of 125 biomarker genes, known as SenMayo biomarkers ( Saul et al 2022 ), to search for evidence of an alteration of cellular senescence associated with various viral infection ( Kaczkowski et al 2012 ; Jagya et al 2014 ; Peng et al 2014 ; Bercovich-Kinori et al 2016 ; Devadas et al 2016 ; Hu et al 2016 ; Tang et al 2016 ; Zhang et al 2016 ; Boldanova et al 2017 ; Deshiere et al 2017 ; Harden et al 2017 ; Hojka-Osinska et al 2017 ; Klymenko et al 2017 ; McGrath et al 2017 ; Oberstein and Shenk 2017 ; Oh et al 2017 ; Razooky et al 2017 ; Viollet et al 2017 ; Zhu et al 2017 ; Journo et al 2018 ; Tso et al 2018 ; Golumbeanu et al 2019 ; Mrozek-Gorska et al 2019 ; Wang et al 2019 ; Blanco-Melo et al 2020 ; Dissanayake et al 2020 ; Li et al 2020 ; Seelbinder et al 2020 ; Sen et al 2020 ; Sheng et al 2020 ; Thompson et al 2020 ; Winer et al 2020 ; Zhuravlev et al 2020 ; Bauby et al 2021 ; Chandrashekar et al 2021 ; Chow et al 2021 ; Coelho et al 2021 ; Dapat et al 2021 ; van der Heijden et al 2021 ; Hong et al 2021 ; Tegtmeyer et al 2021 ; Tsalik et al 2021 ; Yanagi et al 2021 ; Yuan et a...…”
Section: Resultsmentioning
confidence: 99%
“…Samples sources are: (1) Alberts et al (2022) ; (2) Park et al (2022) ; (3) van Solingen et al (2022) ; (4) Chandrashekar et al (2021) ; (5) Chow et al (2021) ; (6) Blanco-Melo et al (2020) ; (7) Deshiere et al (2017) ; (8) Golumbeanu et al (2019) ; (9) van der Heijden et al (2021) ; (10) Bauby et al (2021) ; (11) GSE53993; (12) Coelho et al (2021) ; (13, 14) Devadas et al (2016) ; (15) Bell et al (2022) ; (16) GSE186908; (17) GSE192528; (18) Thompson et al (2020) ; (19, 63–65) Tsalik et al (2021) ; (20, 28, 62) Dissanayake et al (2020) ; . (21) Zhuravlev et al (2020) ; (22) GSE97672; (23, 27) GSE89008; (24) GSE82232; (25) GSE101760; (26) GSE97672; (29) Sheng et al (2020) ; (30) Hong et al (2021) ; (31) Mrozek-Gorska et al (2019) ; (32) Wang et al (2019) ; (33) Yanagi et al (2021) ; (34) GSE84897; (35) Tso et al (2018) ; (36) Journo et al (2018) ; (37) GSE79032; (38) Seelbinder et al (2020) ; (39) Oberstein and Shenk (2017) ; (40–42) Sen et al (2020) ; (43) Zhang et al (2016) ; (44, 49) Jagya et al (2014) ; (45) Yuan et al (2021) ; (46) GSE194179; (47) Zai et al (2022) ; (48) Winer et al (2020) ; (50) Montanari et al (2022) ; (51) Tegtmeyer et al (2021) ; (52) Hojka-Osinska et al (2017) ; (53) Li et al (2020) ; (54) GSE84346; (55) Hu et al (2016) ; (56, 59, 60) Kaczkowski et al (2012) ; (57) Klymenko et al (2017) ; (58) GSE92496; (61) Dapat et al (2021) ; (66) GSE102924; (67) GSE93385; (68) GSE78711; (69) GSE87750. Each column represents a condition of infection, for example, by a given virus in a given human tissue, or successive ti...…”
Section: Resultsmentioning
confidence: 99%